Pigou on the Minimum Wage: An Institutional Inquiry into the Labour Market - Takami, Norikazu (History of economics review, 2009)
In this paper I examine A. C. Pigou's views on the institutional and theoretical aspects of the minimum wage. Pigou acknowledged the need for a minimum wage to redress exceptionally low wages, but this was subject to two provisos: first, when determining the minimum wage, one should not aim for a wage that meets some standard of living; and, second, as the prevailing British trades system of the day provided for differential wage rates for different trades, the coverage of minimum wage must be limited to low-paid workers. Pigou distinguished three types of employees according to their bargaining power and strongly advocated protection for the weakest workers through a minimum wage.